Palmitic acid methyl ester is a novel neuroprotective agent against cardiac arrest. (August 2019) - Lee, Reggie Hui-Chao; Couto e Silva, Alexandre; Possoit, HarLee E.; Lerner, Francesca M.; Chen, Po-Yi; Azizbayeva, Rinata; Citadin, Cristiane T.; Wu, Celeste Yin-Chieh; Neumann, Jake T.; Lin, Hung Wen
Highlights: We previously discovered palmitic acid methyl ester (a C16:0 saturated fatty acid) is a novel and potent vasodilator. We investigated the therapeutic potential of palmitic acid methyl ester against cardiac arrest-induced brain injury and neurological deficits. We found that post-treatment of palmitic acid methyl ester after cardiac arrest can enhance cerebral blood flow and neuronal cell survival ultimately improving functional learning/memory. Abstract: We previously discovered that palmitic acid methyl ester (PAME) is a potent vasodilator first identified and released from the superior cervical ganglion and remain understudied. Thus, we investigated PAME's role in modulating cerebral blood flow (CBF) and neuroprotection after 6 min of cardiac arrest (model of global cerebral ischemia). Our results suggest that PAME can enhance CBF under normal physiological conditions, while administration of PAME (0.02 mg/kg) immediately after cardiopulmonary resuscitation can also enhance CBF in vivo . Additionally, functional learning and spatial memory assessments (via T-maze) 3 days after asphyxial cardiac arrest (ACA) suggest that PAME-treated rats have improved learning and memory recovery versus ACA alone. Furthermore, improved neuronal survival in the CA1 region of the hippocampus were observed in PAME-treated, ACA-induced rats. Altogether, our findings suggest that PAME can enhance CBF, alleviate neuronal cell death, and promote functional outcomes in the presence of ACA.